1995
DOI: 10.1007/bf01204624
|View full text |Cite
|
Sign up to set email alerts
|

Nearwork-induced transient myopia

Abstract: The literature on nearwork-induced transient myopia (NITM) is reviewed, with NITM being defined as the short-term myopic far point shift immediately following a sustained near visual task. A majority of these investigations demonstrated the presence of NITM for a variety of test parameters, e.g., visual acuity, contrast sensitivity and far point. Overall, these studies reported relatively small myopic shifts, with a mean of approximately 0.40 D and a range from 0.12 to 1.30 D. The subsequent decay is character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 41 publications
4
56
0
1
Order By: Relevance
“…It reflects an inability of the crystalline lens to reduce its power appropriately and rapidly, thus reflecting an accommodative aftereffect/hysteresis phenomenon of presumed pharmacologic origin. 5,13 In the normal population, the mean magnitude of NITM is typically sufficiently small (approximately 0.3 D) and remains within the depth of focus of the eye, thus producing no perception of blur. 16,17 One of the first efforts to study NITM was by Lancaster and Williams.…”
mentioning
confidence: 99%
“…It reflects an inability of the crystalline lens to reduce its power appropriately and rapidly, thus reflecting an accommodative aftereffect/hysteresis phenomenon of presumed pharmacologic origin. 5,13 In the normal population, the mean magnitude of NITM is typically sufficiently small (approximately 0.3 D) and remains within the depth of focus of the eye, thus producing no perception of blur. 16,17 One of the first efforts to study NITM was by Lancaster and Williams.…”
mentioning
confidence: 99%
“…21 The NITM is a phenomenon which reflects accommodative after effect/hysteresis after near adaptation. [47][48][49] This is related to a defect of sympathetic inhibition and instability of the crystalline lenses to reduce its power appropriately and rapidly. 47,48 Myopes, especially PMs, tend to show greater magnitude and longer duration of NITM.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] This is related to a defect of sympathetic inhibition and instability of the crystalline lenses to reduce its power appropriately and rapidly. 47,48 Myopes, especially PMs, tend to show greater magnitude and longer duration of NITM. 24,50 During the period of NITM, the image on the retina is in a myopic defocus condition when the subject views a distance target.…”
Section: Discussionmentioning
confidence: 99%
“…10 Few studies have suggested relationship between near work, transient myopia and permanent myopicff. 11,12 Most of these studies have been done in western population and there are limited such studies on the role of cornea in myopia and the association of parental myopia and of near work on myopia in Indian population.…”
Section: Need For the Studymentioning
confidence: 99%